Transient stability enhancement using thyristor controlled series compensator - Surender Reddy Salkuti (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Stability is an important issue which determines the stable operation of power system. At present, the most practical available method of transient stability analysis is time domain simulation, in which the non-linear differential equations are solved by step by step method or network reduction techniques. In this paper, FACTS devices are used  in the existing system for effective utilization of existing transmission resources. In this paper, the studies have been carried out in order to improve the transient stability of 5 bus system, and Western System Coordinating Council (WSCC) 9 bus system with fixed compensation on various lines, and the optimal location has been investigated for better results. To improve the transient stability margin further, a Thyristor Controlled Series Compensator (TCSC) has been used, and the results shows the effectiveness of the application of TCSC in improving the transient stability of power system.